2020
DOI: 10.1111/1758-2229.12916
|View full text |Cite
|
Sign up to set email alerts
|

Conserved bacterial genomes from two geographically isolated peritidal stromatolite formations shed light on potential functional guilds

Abstract: Summary Stromatolites are complex microbial mats that form lithified layers. Fossilized stromatolites are the oldest evidence of cellular life on Earth, dating back over 3.4 billion years. Modern stromatolites are relatively rare but may provide clues about the function and evolution of their ancient counterparts. In this study, we focus on peritidal stromatolites occurring at Cape Recife and Schoenmakerskop on the southeastern South African coastline, the former being morphologically and structurally similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 72 publications
(110 reference statements)
1
20
0
Order By: Relevance
“…While the mat samples harboured a similar cohort of phyla, they were very heterogeneous at the lowest taxonomic level with only 4 ASVs shared among the five lake communities (Figure 3; Table S3) and were distinctly clustered according to their location (PERMANOVA; p = .0001, F = 2.0738) and/or conductivity (PERMANOVA; p = .0002, F = 2.2922) on PCoA ordination (Figure 4). These observations are largely in agreement with previous studies of microbialite‐forming mats from hypersaline Shark Bay, Western Australia (Ruvindy et al, 2016), thrombolites from hypersaline Lake Clifton, Western Australia (Warden et al, 2016), thrombolites (Mobberley et al, 2013), stromatolites from Little Darby Island, The Bahamas (Casaburi et al, 2016), microbialites and non‐ lithifying mats from freshwater habitats along the Trans‐Mexican volcanic belt (Iniesto et al, 2021) and stromatolites from the peritidal eastern coast of South Africa (exposed to both fresh and marine water) (Waterworth et al, 2021). Interestingly, sediment samples were also clustered with mat samples according to lake/conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…While the mat samples harboured a similar cohort of phyla, they were very heterogeneous at the lowest taxonomic level with only 4 ASVs shared among the five lake communities (Figure 3; Table S3) and were distinctly clustered according to their location (PERMANOVA; p = .0001, F = 2.0738) and/or conductivity (PERMANOVA; p = .0002, F = 2.2922) on PCoA ordination (Figure 4). These observations are largely in agreement with previous studies of microbialite‐forming mats from hypersaline Shark Bay, Western Australia (Ruvindy et al, 2016), thrombolites from hypersaline Lake Clifton, Western Australia (Warden et al, 2016), thrombolites (Mobberley et al, 2013), stromatolites from Little Darby Island, The Bahamas (Casaburi et al, 2016), microbialites and non‐ lithifying mats from freshwater habitats along the Trans‐Mexican volcanic belt (Iniesto et al, 2021) and stromatolites from the peritidal eastern coast of South Africa (exposed to both fresh and marine water) (Waterworth et al, 2021). Interestingly, sediment samples were also clustered with mat samples according to lake/conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…The Schoenmakerskop microbialite system comprises mature microbialite formations with an abundance of superficial cyanobacteria as indicated by the diverse mosaic of bacterial taxa reported previously 12,35 and detected here. We found that metabolites and microorganisms differ between core samples of microbialites submerged in the pool throughout the tidal cycle compared to surface microbialites exposed between tides.…”
Section: Discussionmentioning
confidence: 51%
“…These observations motivated us to focus our subsequent analyses on substrate core samples, particularly in light of the known capability of cyanobacteria to produce biologically active metabolites and their central role in structuring microbialite microbial consortia. 16,29,35 Sunburst plots of the CANOPUS output for substrate samples from flag sites 1 (surface) and 7 (submerged) (Fig. S13) display limited divergence of compound superclasses between sites, but revealed significant differences at the class level in metabolites present at each site.…”
Section: Metabolite Diversity Of Substrate Cores Compared To Tom In T...mentioning
confidence: 99%
See 1 more Smart Citation
“…The closest matches in the antiSMASH database of microbial secondary metabolites [ 32 ] were paenibactin and myxochelin. Homologs of these genes were detected by BLAST in an assembly of the cyanobacterium Leptolyngbya from metagenome data obtained for a South African peritidal stromatolite (NCBI BioProject PRJNA612530, assembly SM1_1_3) [ 77 ]. It is not clear whether this cluster was inherited from a common ancestor or independently acquired.…”
Section: Resultsmentioning
confidence: 99%